Analysis of protein dynamics with tandem fluorescent protein timers - Khmelinskii, Anton; Knop, Michael (Exocytosis and Endocytosis, 2014)
Fluorescent timers (FTs) are fluorescent proteins that change color with time. FTs can be used as tags to follow protein dynamics in living cells. Recently we described a novel class of FTs called tandem fluorescent protein timers (tFTs). Each tFT is a tandem fusion of two different conventional fluorescent proteins having distinct kinetics of fluorophore maturation. tFTs suitable for studying protein dynamics on different scales can be generated from a broad range of commonly used fluorescent proteins. Here we describe how to establish new tFTs and consider potential pitfalls. We detail a protocol for quantitative fluorescence microscopy imaging and analysis of intracellular protein dynamics with tFTs in the budding yeast Saccharomyces cerevisiae.
Gesehen am 09.08.2017